Liquefaction potential hazard study at UIN Datokarama, Palu City, Central Sulawesi - Mulki Azmi; Rifa’i Ahmad; Ismanti Sito (E3S Web of Conferences, 2023)
In June 2019, the Asian Development Bank approved emergency rehabilitation and reconstruction assistance (EARR) to help Indonesia rebuild better critical infrastructure damaged by the 2018 Palu-Donggala earthquake. One of the EARR sub-projects is the reconstruction of Universitas Islam Negeri (UIN) Datokarama that suffered significant damage from the combined effects of the tsunami and earthquake. The design for the building's reconstruction incorporated better principles of deconstruction, including pile foundations to ensure the facilities are earthquake, tsunami, and liquefaction resistant. This study purpose is to evaluate liquefaction potential and estimate its severity or damage potential to structures in the reconstruction site. Liquefaction potential will be assessed in two ways, first by using soil deposits grain sizes distribution method from Japan technical standards for port and harbour facilities and second by safety factor against liquefaction (FOS) method using the SPT-based liquefaction triggering analysis with the revised magnitude scaling factor (MSF) relationship by Idriss and Boulanger. Liquefaction Potential Index (LPI) from Iwasaki will be used for estimating liquefaction severity. The analysis is performed on dataset taken from 6 boreholes in location dominated by saturated sandy soil and shallow ground water. Based on the result, liquefaction potentially triggered at various depth with consistent LPI index at > 15, The reconstruction site has a very high liquefaction risk.